The influence of profitability, business risk, corporate governance on dividend policy with growth opportunity as a moderation variable (lq45 companies listed on the bei) - Theliya, Theliya; Azazi, Anwar; Malini, Helma; Daud, Ilzar; Wendy, Wendy (Institute of Computer Science (IOCS), 2024)
LQ45 is a stock index company listed on the Indonesian Stock Exchange with high liquidity which is selected based on certain criteria or choices. Companies that are included in the criteria include having financial condition, transaction value and a high growth rate. These criteria can be seen through the company's dividend policy. Factors that influence dividend policy are profitability, business risk, corporate governance, apart from that, the existence of growth opportunities can provide opportunities for companies to grow and develop in the future. This research will examine how much influence profitability, business risk, corporate governance have on dividend policy, with growth opportunity as a moderating variable. The financial data for this study came from a number of financial reports that are filed on the Indonesia Stock Exchange (BEI). The LQ45 firm index category, which is listed on the BEI for the 2018–2022 period, serves as the population of interest for this study, and the sample size is limited to 20 companies. Descriptive statistical analysis, multiple linear regression analysis, coefficient of determination analysis, simultaneous test (F), partial test (T), and the classical assumption test are the data analysis methods employed in this study. Based on moderator regression analysis (MRA), a method of data processing. It is proven that profitability influences dividend policy with positive and significant results, while business risk and corporate governance do not have a significant influence on dividend policy. Profitability, business risk, corporate governance, after being moderated by growth opportunity, do not have a significant effect on dividend policy.